Vasa nervorum angiogenesis in prostate cancer with perineural invasion. Issue 6 (20th January 2019) - Ghinea, Nicolae; Robin, Blaise; Pichon, Christophe; Leclere, Renaud; Nicolas, André; Chnecker, Caroline; Côté, Jean‐François; Guillonneau, Bertrand; Radu, Aurelian
Abstract : Background: Perineural invasion (PNI) is generally accepted as a major route of cancer dissemination in malignancies associated with highly enervated organs. However, the effect of cancer cells on vasa nervorum remains unknown. We studied this effect in locally advanced prostate cancer, a high‐risk feature associated with approximately 20% of prostate cancer specific mortality. Methods: We used immunohistochemistry for CD34, fibroblast growth factor‐2 (FGF‐2), FSHR, podoplanin, vascular endothelial growth factor (VEGF), and VEGFR‐2 as well as histochemical methods to examine the vasa nervorum of nerves invaded by cancer cells in tissue samples from 85 patients. Results: The percentage of the nerve area occupied by CD34‐positive vasa nervorum endothelial cells in nerves with PNI was much higher than in nerves without PNI (7.3 ± 1.2 vs 1.9 ± 0.4; P < 0.001 and 5.8 ± 0.6 vs 1.23 ± 0.8; P < 0.001 in pT3a and pT3b prostate cancer specimens, respectively). In 19/85 of the patients the CD34‐positive vasa nervorum microvessels have a thick basement membrane, similar to the vessels in diabetic microangiopathy. This subendothelial layer contains collagen fibers. Vasa nervorum endothelia and Schwann cells express FGF‐2 (nuclear localization) and FSHR (plasma membrane and cytoplasmic staining). Prostate cancer cells invading nerves express VEGF, a critical cytokine in tumor angiogenesis. The vasa nervorum of prostatic nerves with PNI did not express detectable levels of VEGFR‐2. No podoplanin‐positive lymphatic vessels were seen in nerves. Conclusion: In locally advanced prostate cancer, PNI of cancer cells is associated with formation of new endoneurial capillaries and changes of vasa nervorum morphology.